2022
DOI: 10.3390/ijms23147718
|View full text |Cite
|
Sign up to set email alerts
|

CALMODULIN1 and WRKY53 Function in Plant Defense by Negatively Regulating the Jasmonic Acid Biosynthesis Pathway in Arabidopsis

Abstract: Jasmonic acid (JA) is an important hormone that functions in plant defense. cam1 and wrky53 mutants were more resistant to Spodoptera littoralis than in the wild-type (WT) Arabidopsis group. In addition, JA concentration in cam1 and wrky53 mutants was higher compared with the WT group. To explore how these two proteins affect the resistance of Arabidopsis plants, we used a yeast two-hybrid assay, firefly luciferase complementation imaging assay and in vitro pull-down assay confirming that calmodulin 1 (CAM1) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In addition, in vitro interaction has been described for MAPKKK19 with PEN3, an ABC transporter involved in exporting antimicrobial metabolites ( Campe et al., 2016 ). Likewise, MAPKKK20 interacts in vitro with several calmodulin-like proteins ( Popescu et al., 2007 ), such as CAM1, recently described as a negative regulator of JA biosynthesis ( Jiao et al., 2022 ). The biological implications of these interactions should be demonstrated in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in vitro interaction has been described for MAPKKK19 with PEN3, an ABC transporter involved in exporting antimicrobial metabolites ( Campe et al., 2016 ). Likewise, MAPKKK20 interacts in vitro with several calmodulin-like proteins ( Popescu et al., 2007 ), such as CAM1, recently described as a negative regulator of JA biosynthesis ( Jiao et al., 2022 ). The biological implications of these interactions should be demonstrated in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…The resistance of Arabidopsis to S. littoralis herbivory has been studied by focusing on CALMODULIN1 (CAM1) and WRKY53 function. Yingbai Shen and co-workers [10] confirmed that CAM1 interacts with the transcription factor WRKY53, which in turn binds to the promoter regions of lipoxygenases 3 (LOX3) and lipoxygenases 4 (LOX4) by negatively regulating their gene expression. Eventually, the plant resistance to herbivory is negatively regulated by CAM1 and WRKY53 through regulation of the JA biosynthesis pathway.…”
Section: Spodoptera-plant Interactionsmentioning
confidence: 96%
“…wrky53 shows enhanced disease susceptibility, while WRKY53‐ overexpression mutants display enhanced resistance to pathogens, suggesting that WRKY53 plays a positive role in plant immunity (Murray et al, 2007). WRKY53 also negatively regulates plant defense against insects by negatively regulating the expression of lipoxygenase 3 (LOX3) and LOX4 which are associated with the biosynthesis of JA (Jiao, Li, et al, 2022). Further studies are required to elucidate the linkage between Ca 2+ /CaM signalling and the functions of these CaM‐binding TFs in plant defenses against pathogens and/or herbivores.…”
Section: Cam‐binding Proteins: Downstream Targets Of Cams/cmlsmentioning
confidence: 99%